2010
DOI: 10.1093/logcom/exq030
|View full text |Cite
|
Sign up to set email alerts
|

Two new homomorphism dualities and lattice operations

Abstract: The study of constraint satisfaction problems definable in various fragments of Datalog has recently gained considerable importance. We consider constraint satisfaction problems that are definable in the smallest natural recursive fragment of Datalog -monadic linear Datalog with at most one EDB per rule, and also in the smallest non-linear extension of this fragment. We give combinatorial and algebraic characterisations of such problems, in terms of homomorphism dualities and lattice operations, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The first of these examples covers all problems Min CSP(Γ) that were previously known to belong to APX. Two classes of CSPs were introduced and studied in [10], one is a subclass of the other. We need two notions to define these classes.…”
Section: Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these examples covers all problems Min CSP(Γ) that were previously known to belong to APX. Two classes of CSPs were introduced and studied in [10], one is a subclass of the other. We need two notions to define these classes.…”
Section: Algorithmsmentioning
confidence: 99%
“…Constraint languages k -IHBS (defined in Section 1) belong to the larger, but not to the smaller class (see Example 1). See [10] for other specific examples of CSPs contained in these classes. For the smaller class, Min CSP(Γ) was shown to belong to APX in [32].…”
Section: Algorithmsmentioning
confidence: 99%
“…We first describe the characterization of lattice CSPs we need. Carvalho, Dalmau, and Krokhin [5] have observed that if CSP(Γ) has lattice polymorphisms then it is preserved by what they call an absorptive block-symmetric operation. This is an operation f which takes as input tuples (of any…”
Section: A Lattice Csps: Better Quantitative Dependence Onmentioning
confidence: 99%
“…Another family of problems CSP(Γ) with bounded pathwidth duality was shown to admit robust algorithms with polynomial loss in [23], where the parameter k depends on the pathwidth duality bound (and appears in the algebraic description of this family). This family includes languages not having an NU polymorphism of any arity -see [13,14]. It is unclear how far connections between the two directions go, but consistency notions seem to be the common theme.…”
Section: Resultsmentioning
confidence: 99%